1, 2-Dichloroethane induces cerebellum granular cell apoptosis via mitochondrial pathway in vitro and in vivo. (1st April 2020) - Huang, Manqi; Zhong, Yizhou; Lin, Li; Liang, Boxuan; Liu, Jun; Jiang, Junying; Hu, Manjiang; Huang, Yuji; Lin, Xi; Lu, Lvliang; Bian, Ziwei; Zhong, Wenyu; et al.
Highlights: 1, 2-DCE inhibited cell viability on HCGCs and induced apoptosis-mediated cell death. 1, 2-DCE altered HCGC proteins expression of Caspase-3, cleaved Caspase-3, Cytochrome c, Bad. 1, 2-DCE induced significantly shrunken, hypereosinophilic cytoplasm with nuclear pyknosis in CGCs. Abnormal neurobehavioral changes were found in mice exposed to 1, 2-DCE. 1, 2-DCE induced apoptosis by activation of mitochondrial pathway in mouse cerebella. Abstract: 1, 2-Dichloroethane (1, 2-DCE) is a widely used chlorinated organic toxicant, but little is known about the cerebellar dysfunction induced by excessive exposure to it. To uncover 1, 2-DCE-induced neurotoxicity in cerebellar granular cells (CGCs), and to investigate the underlying mechanisms, we explored this, both in vitro and in vivo . Our findings showed significant cell viability inhibition in human CGCs (HCGCs) treated with 1, 2-DCE. Flow cytometry and mitochondrial membrane potential analyses discovered an increase in apoptotic-mediated cell death in HCGCs after 1, 2-DCE treatment. This HCGC apoptosis was involved in the increases of protein expression in Cytochrome c, Caspase-3, Bad, Bim, transformation related protein 53, Caspase-8, tumor necrosis factor-α, and Survivin. Quantitative real-time PCR (qPCR) and western blot confirmed the increases in Cytochrome c, Caspase-3, cleaved Caspase-3, and Bad in HCGCs after 1, 2-DCE treatment. Bax inhibitor peptide V5 rescued 1, 2-DCE-induced HCGC apoptosis. Furthermore, 80 CD-1 male mice were exposed to 1, 2-DCE by inhalation at 0, 100, 350, and 700 mg/m 3 for 6 h/day for 4 weeks. An open field test found abnormal neurobehavioral changes in the mice exposed to 1, 2-DCE. Histopathological examination showed significantly shrunken and hypereosinophilic cytoplasm with nuclear pyknosis in mouse CGCs from the 700 mg/m 3 1, 2-DCE group. TdT-mediated dUTP nick-end labeling assay verified significant increases in apoptotic positive cells in the mouse CGCs after 1, 2-DCE exposure. We confirmed the increases in the expressions of Cytochrome c, Caspase-3, cleaved Caspase-3 and Bad in the mice exposed to 1, 2-DCE. These findings suggest that 1, 2-DCE exposure can induce CGC apoptosis and cerebellar dysfunction, at least in part, through mitochondrial pathway.